CONTINUITY OF UNDERGRADUATE AND GRADUATE PROGRAMS AS A KEY FACTOR OF THE QUALITY ASSURANCE IN HIGHER EDUCATION - V. S. Senashenko; N. A. Pykhtina (Moscow Polytechnic University, 2018)
The paper discusses the conditions and mechanisms to ensure the continuity of basic undergraduate and graduate educational programs as a prerequisite for quality assurance in higher education. The authors consider various approaches to the practical realization of master's programs, the requirements for successful formation of the system of continuous education in the conditions of introduction of multilevel structure of educational programs. The paper dwells on the specificity of educational process organization, especially on the difficulties caused by the non-compliance of the continuity principle in coupling undergraduate and graduate programs.